Analyzing Factors Influencing Volunteer Experience in Large-Scale Sporting Events - Michael Fysentzidis; Athanasios Strigas; Lazaros Ntasis (Asociación Española de Ciencias del Deporte, 2024)
Despite the extensive literature on volunteers at sports events, there remains limited comprehension among researchers regarding volunteer experience. While studies suggest direct and indirect relationships between motivation, satisfaction, commitment, and sense of community concerning volunteer experience, empirical understanding in this area remains inadequate. The primary objective of this research was to empirically examine the relationship between external influence, satisfaction, and the sense of sports event volunteers' experiences. Following the "Athens Marathon, The Authentic," 850 volunteers participated in an online self-administered questionnaire, yielding a response rate of 65%. Hypothesized linear relationships were tested using a two-step structural equation model. The findings reveal both direct (external influence and satisfaction) and indirect (commitment and sense of community) connections leading to volunteer experience. Volunteer satisfaction demonstrates an indirect relationship with material, mediated by the direct relationship with external influence. Similarly, the sense of egoism exhibits an indirect relationship with volunteer satisfaction, mediated by direct external influences. Additionally, the study identifies leisure as the sole determinant of the direct relationship with satisfaction. Overall, the study emphasizes the necessity of comprehensive analyses to account for the interconnected nature of factors influencing volunteer satisfaction.